Effects of grinding media shapes on ball mill performance - Lameck, Niyoshaka Nistlaba Stanley (My University, 2006)
Comminution is an important process in mineral processing, power plants, cement production and pharmaceutical industries. It is costly and an inefficient process in terms of energy requirements and steel consumption related to grinding media and liners. Spherical grinding media are predominantly used in final stages of ore grinding. The spherical balls change shape through breakage and wear. Though this is universal in milling, its contribution and effect on milling kinetics, load behaviour and mill power is not fully established. One area that is usually ignored is the relationship between media shape and mill power. The objective of this dissertation was to investigate how media shape affects grinding. Ball size distribution inside an industrial mill was analysed in terms of shapes and sizes. Load behaviour, mill power and breakage as affected by media shapes were studied in a pilot laboratory mill. An inductive proximity probe, light emitting diode, phototransistor and video photographs were used to determine the load orientation in terms of toe and shoulder positions. A load beam was used to measure the torque exerted by the charge. The variation in load orientation and mill power with speed among different media shapes was observed. Higher shoulder positions were noted with cylpebs than with worn and spherical balls. The power increased to a maximum with increasing mill speed for all media shapes reaching its peak at different mill speeds for the three shapes studied. Variations of breakage rates with media shapes were found; higher breakage rates were noted with spherical media but the differences narrows with decreasing feed size and increasing material fractional filling U. Considering that worn balls in an industrial mill charge constitute about 15 to 40 percent and that the highest difference in breakage rate observed being nine percent for purely one shape charge; it is very doubtful whether it is worthwhile in attempting to develop techniques for removing worn balls from the mill.
Student number : 0318567G School of Chemical and Metallurgical Engineering Faculty of Engineering
Keywords: grinding; comminution; power; load behaviour; grinding media; breakage kinetics